Calibration Issue in SMART Synthetic Aperture Radar Based on Scan-On-Receive - Bordoni, Federica; Marwan, Younis; Krieger, Gerhard (Advanced RF Sensors for Earth Observation (ARSI), 2009)
A new spaceborne Synthetic Aperture Radar (SAR) system based on SCan-On-REceive (SCORE) algorithm has been recently proposed in order to overcome the trade-off between spatial resolution and swath wide of current SAR systems. The compound architecture of the receiver, which employs multiple channels and Digital Beam-Forming technique, places new challenges to spaceborne SAR internal calibration (Cal) and requires the definition of a new Cal approach. In this paper a novel method for onboard internal Cal of the multichannel receiver of a SAR system based on SCORE is proposed and numerically analyzed.
DLR Import::2019-04-03